SINERGITAS RENCANA KERJA PEMERINTAH DAERAH DENGAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (Studi Pada Kabupaten Rembang) - Tahwin, Muhammad (Potensio, 2013)
This study aims to analyze the synergy ofÂ  regional development work plan with regional medium, term development plan in Rembang Regency. The analysis method used in this study is qualitative descriptive analysis method. The result of the study shows that the percentage of regional development work plan wich synergies with regional medium term development plan is 16%. There are two priority programs in rembang regency in 2009 that do not synergize with regional medium term development plan in 2006-2010.Keywords: regional development work plan, regional medium term development planÂ